SISTEM AKUISISI DATA MULTI KANAL UNTUK PENGAMBILAN DATA SENSOR SECARA SIMULTAN - Veronika Siallagan; Lazuardi Umar; Rahmondia Nanda (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This research aims to operate an instrument system acquisition data multi channel by measuring the humidity sensors grounded by using gypsum. The censorship is made of gypsum material printed as cylindrical shape with a diameter (d) of 18 mm and length (l) of 20 mm. The circuit of main equipment uses microcontroller based on ATmega8 that can operate from 2.7 Volt until 5.5 Volt. It can be passed by the current of 3.6 A and integrated to ADC type ADS7822 and DAC7611 with high voltage of 4.96 volt. The circuit of programme uses an application WinAvr with Language C. By operating the instrument system, the acquisitions data 16 channels tested at agricultural land from the regions Kartama. The circuit was operated on moisture land of 15%, 20%, 25%, and 30% compared with Lutron Kallibrator. After testing that equipment a general Equation was obtained, where this mathematical model can describe the relationship between the electrodes of voltage (Uo) of moisture land (èw). The Equation obtained from the testing is the empirical solution depending on soil type.